2021
DOI: 10.1515/nanoph-2021-0501
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable terahertz metasurfaces coherently controlled by wavelength-scale-structured light

Abstract: Structuring light–matter interaction at a deeply subwavelength scale is fundamental to optical metamaterials and metasurfaces. Conventionally, the operation of a metasurface is determined by the collective electric polarization response of its lithographically defined structures. The inseparability of electric polarization and current density provides the opportunity to construct metasurfaces from current elements instead of nanostructures. Here, we realize metasurfaces using structured light rather than struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Wavefront shaping in the THz, in the extreme ultraviolet, and in the x-ray ranges, for instance, can be achieved by using a SLM to control the visible input field. In the THz range, for instance, nonlinear optical conversion from visible light is already used to generate [35] and detect [36] THz fields, and a scheme to optically control metasurfaces generating THz radiation has been recently demonstrated [37]. In addition, wavefront sensing of telecom and x-ray fields can be accomplished by conversion to the visible range.…”
Section: Discussionmentioning
confidence: 99%
“…Wavefront shaping in the THz, in the extreme ultraviolet, and in the x-ray ranges, for instance, can be achieved by using a SLM to control the visible input field. In the THz range, for instance, nonlinear optical conversion from visible light is already used to generate [35] and detect [36] THz fields, and a scheme to optically control metasurfaces generating THz radiation has been recently demonstrated [37]. In addition, wavefront sensing of telecom and x-ray fields can be accomplished by conversion to the visible range.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum control is an effective way to generate and control currents in semiconductors by exploiting quantum interference between pathways connecting the same initial and final states (14)(15)(16). In our previous experiments, we have demonstrated structured current generation by applying spatially structured light pulses to quantum control (17)(18)(19)(20). We have also shown that almost any kind of current patterns can be generated using a combination of a circularly polarized near-infrared pulse and a linearly polarized visible light pulse whose phase front has been structured by a spatial light modulator (18,19).…”
Section: Introductionmentioning
confidence: 98%
“…In our previous experiments, we have demonstrated structured current generation by applying spatially structured light pulses to quantum control (17)(18)(19)(20). We have also shown that almost any kind of current patterns can be generated using a combination of a circularly polarized near-infrared pulse and a linearly polarized visible light pulse whose phase front has been structured by a spatial light modulator (18,19). Each transient current element acts as a subwavelength source of the THz field and a large collection of such transient current elements constitutes an active metasurface that radiates structured, single-cycle THz pulses.…”
Section: Introductionmentioning
confidence: 99%
“…The phase delay of the two pulses was shown to control interference between the two-photon (ω) and single-photon (2ω) pathways and to finally determine the direction of electron motion [2]. However, this optical technique limits the dimen-sions over which the electron current is generated to roughly one wavelength of the infrared light that is used to accelerate the electrons [14], i.e., to a few μm. Using coherent control of one-and two-photon processes to reduce to the nm scale the dimensions over which current is produced requires optically generating ω and 2ω vacuum ultraviolet (VUV) light beams.…”
Section: Introductionmentioning
confidence: 99%